Satisfacción de los usuarios por los servicios prestados por el Hospital Martín Icaza de la ciudad de Babahoyo - Fajardo Manzaba, José Ignacio (2019)
This case study is directed towards the Martin Icaza hospital, which is a public establishment located in the city of Babahoyo, Los Ríos province. The hospital serves not only users from the province of the Ríos but also other provinces such as Bolívar and Guayas. The case study is framed in the research line of administrative management model carried out through qualitative research, aims to know the level of quality of care, the type of equipment in the care it provides from its collaborators and the degree of user satisfaction for the care received at the Martin Icaza hospital in the city of Babahoyo